Two low-dose bowel-cleansing regimens: efficacy and safety of senna and sodium phosphorus solution for colonoscopy - Poyrazoglu, Orhan Kursat; Yalniz, Mehmet (Dove Medical Press Ltd, 2015)
Background: The aim of the present study was to compare the efficacy, adequacy, side effects, and patient compliance of sodium phosphorus (NaP) and senna solutions when preparing the colon before colonoscopy. Methods: A total of 137 consecutive patients who were considered for colonoscopy evaluation had randomly received one of two premeditated regimens: 90 mL of oral NaP (NaP group) or 500 mL of 1,000 mg of sennosides A and B calcium +66.6 g of sorbitol (senna group). Patients' compliance with the bowel-cleansing method was determined using a questionnaire prior to the colonoscopic examination. On the other hand, the adequacy of the bowel-cleansing method was evaluated by the colonoscopist who was blind to the bowel-cleansing regimen used prior to the examination of the colon from the rectum to the cecum. Results: Nausea and vomiting complaints were seen more frequently in the NaP group than in the senna group (47 vs 28 and 31 vs 10; P<0.05 and P<0.01, respectively). The response to the question of whether the patients would like to use the same regimen again or not was similar in both groups. The acceptable bowel-cleansing rate was also comparable across both groups. Nevertheless, the number of patients that experienced excellent bowel cleansing in terms of general appraisal of the colonoscopic evaluation was significantly greater in the NaP group than in the senna group (46 vs 25; P<0.001). Conclusion: Although bowel cleansing was better in the NaP group, both cleansing regimens were comparable regarding the admissibility of the preparations for the procedure. The senna regimen is, however, superior to the NaP regimen in terms of application compliance and its side effects, and it may be an effective alternative for cleansing the bowel prior to colonoscopic examination.
Keywords: bowel preparation; colonoscopy; side effect; senna; sodium phosphorus